Influencia de posturas forzadas sobre la salud ocupacional de odontólogos. Distrito Salud 06d01 Chambo-Riobamba - Diego Mauricio, Higuera Sánchez (2021)
ABSTRACT The main objective of this research project was to analyze the influence of forced postures on the occupational health of dentists in Health District 06D01 Chambo-Riobamba, for which a descriptive, exploratory, observational and non-experimental study was carried out with a mixed and cross-sectional approach. The study sample consisted of 37 dentists who met the selection criteria. The techniques used were observation for the recording of forced postures using the OWAS method checklist as an instrument, in addition the survey technique was used using the NEK questionnaire as an instrument; the data were processed in the SPSS v.25 statistical program. The results showed dominant forced postures, in the back of type turned or laterally inclined in 51.4%, arms one above or at shoulder level in 86.5%, the position of legs 100% worked seated and handled a force less than or equal to 10 kilograms, 76% corresponds to a risk level 2 while 24% to a risk level 3; The predominance of pain in the professionals was significantly in the dorsal-lumbar area in 80.1% followed by the neck area in 70.3% and in smaller percentages in the shoulder, wrist or hand, and elbow or forearm. No association or relationship was found between the discomfort in the neck and back and the dorsal or lumbar part and the risk category (p=0.571; p=0.492). Keywords: Influence, forced postures, occupational health Reviewed by: Mgs. María González Rodríguez ENGLISH PROFESSOR C.C. 0603333333